Model Pembelajaran Blended Learning Tipe Flipped Classroom Untuk Meningkatkan Hasil Belajar - Khusna, Mufidatul; Febrianto, Priyono Tri (Universitas Muhammadiyah Magelang, 2023)
This research is rooted in low achievement in the cognitive realm of science subjects with gravitational force material in grade IV elementary schools. The main purpose of this research is to investigate the improvement of student learning outcomes in science subject disciplines related to the concept of gravity force through the application of a flipped classroom type blended learning learning model. The focus of this research is centered in one of the public elementary schools in Bangkalan Regency, Madura. This research adopts a mixed approach that integrates qualitative and quantitative elements. The method applied is Classroom Action Research (PTK) with two stages of cycles. The subjects of the study involved 31 grade IV elementary school students, with details of 16 boys and 15 girls. Research data were obtained through observation techniques and tests. The findings of this research revealed a substantial improvement in the learning outcomes of students in science subjects gravitational force material through the application of a flipped classroom type blended learning model. This is known from the students' classical completion rate which increases in each phase: pre-cycle (29%), cycle 1 (58%), and cycle 2 (94%). These data reflect consistent improvements in student learning outcomes in each cycle. This is proof that the application of the flipped classroom type blended learning model is effective in improving student learning outcomes.